Trade, Competitiveness and Finance in the Philippine Manufacturing Sector, 1980-1995 - Josef T. Yap (Philippine Institute for Development Studies (PIDS), 1999)
The East Asian miracle of the 1960s up to the mid 1990s and the East Asian debacle in 1997 put into perspective two crucial factors that affect sustainable economic growth and development. The first is outward orientation necessary for increasing the competitiveness of an economy and second is the sound financial structure necessary for efficient resource allocation and macro stability. The concern of this paper is to analyze how these two factors interact with each other with a focus on the trade sector, particularly the manufacturing exports, and the dynamics of its competitiveness.
Keywords: 330; total factor productivity; manufacturing sector